Quantitative Strategic Planning Matrix Analysis On The Implementation Of Second Screen Technology - Jarot S Suroso; Hitori A. Fatchan (IAES Indonesia Section, 2018)
A massive technological development requires the company to make strategic changes to compete to survive. In order for companies to survive we need a competitive business advantage to increase Performance Excellence. Similarly, for the PT. Visi Media Asia with its business unit in the field of television, tvOne. In determining and implementing a strategy to compete need to do some analysis. The analytical tool that used in this thesis is IE matrix, SWOT, and QSPM analysis. The internal factor analysis produce the main strength of this company is the company products are loved by people with a score of 0,61. While the company has a major weakness, namely the distribution of technology products is left behind with a score of 0,63. The Merger of internal factors on the company generated an average score of 2,90. External factor analysis (EFAS) generate major opportunities that can be utilized by the company is the development of technology of rapid product distribution with a score of 0,72. While the company's main threat gained from research that people are beginning to switch to digital media than conventional television viewing with a score of 0,63. Merging these two external factors in PT. Visi Media Asia result the average score of 3,12. Based on the SWOT matrix, produced five strategies that can be done by PT. Visi Media Asia on the TV business, tvOne. QSPM processing results is produce the most interesting strategies to be used as a competitive strategy by companies that make technological breakthroughs that can bridging between digital and analog media with TAS value of 7,07.